(3GdHgLI GdCfSjI aj GdaQGSI GdEfSGfjI hGdHgLI GdeQVjI aj GdaQGSI GdCjeGfjIs - (3eMeO Hf eMeO Rjf GdYGHOjf GdCTYQj GdZeQj SHW GdeQUaj , Rjf GdYGHOjf,J (B966 (3g` s
(3ChdgG (B:s
(3hHYO , aEfi ai gPG GdJUfja HChLR YHGQI hCMSf JQUja eG jfHF Ydi GdaQGSI GdGjeGfjI hjDPf HGdaQGSI GdcTajI s
(3BNQgG (B:s
(3aGdMPQ GdMPQ ef HWT Gdedc GdLHGQ bHd GdahGJ HGdNQhL ef gPG GdOGQ s
(3Gjg fSNI CNQi efg ai (B51 (3hQbI heSWQJgG (B15 (3SWQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B58 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B257 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B246s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B137 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGSI (B3) s
Keywords: (3GdaQGSIs